Dinosaur roar! - Stickland, Paul. (New York : Dutton Children's Books, 1994)
Illustrations and rhyming text present all kinds of dinosaurs, including ones that are sweet, grumpy, spiky, or lumpy.
"First published in the United States 1994 by Dutton Children's Books."
Keywords: Dinosaurs -- Juvenile fiction; Dinosaurs -- Fiction; Stories in rhyme